2004
DOI: 10.1021/jp047056q
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Hydrogen Storage in Carbon Nanotubes Promoted by Metal Catalysts

Abstract: Atomic hydrogen storage by carbon nanotubes (CNTs) at atmospheric pressure is studied using Pd and La catalysts for dissociation of H 2 into atomic hydrogen and formation of defects on CNT surfaces, respectively. The defect sites on CNTs as adsorption sites of atomic hydrogen are prepared by oxidation pretreatment using a La catalyst. Pd catalysts are then deposited on CNT surfaces for dissociation of H 2 into atomic hydrogen, which then spills over to the defect sites. In the best case, 1.0 wt % hydrogen is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 35 publications
4
114
1
1
Order By: Relevance
“…1, the pristine MWCNTs have the lowest onset and offset temperatures among the other samples. Yoo et al reported the rate of catalyst role in the starting of MWCNT oxidation at lower temperature [22]. Also, Chen et al reported that the oxidation stability of carbon nanotubes is influenced by defect sites in graphite and nanotube diameters [21].…”
Section: Resultsmentioning
confidence: 99%
“…1, the pristine MWCNTs have the lowest onset and offset temperatures among the other samples. Yoo et al reported the rate of catalyst role in the starting of MWCNT oxidation at lower temperature [22]. Also, Chen et al reported that the oxidation stability of carbon nanotubes is influenced by defect sites in graphite and nanotube diameters [21].…”
Section: Resultsmentioning
confidence: 99%
“…However, a number of experiments indicate that doping porous carbon materials (nanotubes, nanofibers, nanoporous carbons) with metallic clusters or nanoparticles could provide a strategy to increase the hydrogen uptake. [18][19][20][21][22][23][24][25][26] The metals mostly used in those investigations are alkali metals 18,19 and some transition metals like vanadium, palladium, and platinum. [22][23][24][25][26][27] To explain the observed enhancement of the hydrogen adsorption, a mechanism of spillover 28,29 has generally been assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Our methodology here of the hydrogen storage is to adsorb atomic hydrogen at the defect sites of CNTs after dissociation of H 2 by Pd catalyst particles attached to the CNTs [15][16][17]. La catalysts have been doped to CNTs in order to introduce the defect sites [17], which catalyze oxidation of CNTs by O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…La catalysts have been doped to CNTs in order to introduce the defect sites [17], which catalyze oxidation of CNTs by O 2 . We have used thick MWCNT for the atomic hydrogen storage, because the defect density on the wall of MWCNTs is expected to be much more than that on SWCNTs or thin CNTs and because MWCNTs can be obtained at low cost by catalytic decomposition of hydrocarbons as a mass production.…”
Section: Introductionmentioning
confidence: 99%